Effects of behavior-specific praise training on one-on-one paraprofessional-student dyads - Spurlock, Kassandra R.; Brandon, Carrie L.; Mathur, Sarup R. (Frontiers in Education, 2024)
In special education, some students with significant needs require one-on-one adult support from a paraprofessional. However, these paraprofessionals often lack adequate training and support. Special education teachers frequently report feeling unprepared and ill-equipped to provide the necessary training. To address this, we used a multiple-baseline across participants design to examine the effects of a paraprofessional training program on rates of behavior-specific praise (BSP), student on task behaviors, and paraprofessionals' reported levels of confidence in supporting behaviors. Participants were three paraprofessional-student dyads consisting of a oneon-one paraprofessional and a first or second grade student with special needs at an urban public school serving grades PreK-3. The intervention program included BSP training, role play, and case discussion. One paraprofessional also required an additional coaching element. Visual analysis of the data indicated that the intervention was effective in increasing rates of paraprofessional delivered BSP, but did not have a clear impact on student on-task behaviors.The study highlights the importance of ongoing professional development and support for paraprofessionals in implementing evidence-based strategies.